Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in aortic stenosis - Is this the light at the end of the tunnel for patients with aortic stenosis? - Agstam, Sourabh (Indian Heart J, 2021)
The exploratory analysis of FOURIER trial has offered a ray of hope for patients with nonrheumatic aortic stenosis (AS). At present, the only definitive treatment of severe AS is aortic valve replacement (AVR). Despite transaortic valvular replacement revolutionizing the treatment of AS, it still remains a progressive condition, with no disease-modifying pharmacotherapy. Angiotensin-converting-enzyme inhibitors, angiotensin receptor blockers, eplerenone, nitrates and statins all have been tried previously but failed to slow down the progression of aortic stenosis. Recently, there has been an emerging role of lipoprotein A [Lp(a)] in the pathogenesis of AS. This raises the possibility that long-term therapy with specific emphasis on Lp(a) reduction may reduce or slow the progression of AS.